Method for producing composite particles
By stabilizing a liquid core particle precursor with micronized cellulose and organic onium cations, the method addresses the low solid content and handling issues of CNF dispersions, resulting in easily handleable and versatile composite particles with improved efficiency and stability.
Patent Information
- Application Number
- JP2021529995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-01
- Filing Date
- 2020-06-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-06-26
AI Technical Summary
Existing cellulose nanofiber (CNF) dispersions have low solid content concentrations, leading to high transportation costs, compatibility issues with resins, and difficulty in compounding due to solvent incompatibility, along with challenges in handling and stability during storage and use.
The production of composite particles by stabilizing a liquid core particle precursor with micronized cellulose having anionic functional groups and organic onium cations, forming a Pickering emulsion that is solidified to create uniformly coated, easily handleable, and versatile particles.
The method results in composite particles with high solid content concentrations, reducing transportation costs, improving addition efficiency, and maintaining dispersion stability, while allowing for a wide range of resin applications and easy redispersion.
Smart Images

Figure 0007601352000005 
Figure 0007601352000006 
Figure 0007601352000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite particle comprising finely divided cellulose and a core particle. Manufacturing method Regarding. This application claims priority based on Japanese Patent Application No. 2019-122831, filed on July 1, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, active efforts have been made to refine the cellulose fibers in wood so that at least one side of the structure is on the order of nanometers and to utilize them as new functional materials.
[0003] For example, Patent Document 1 discloses that wood cellulose can be repeatedly mechanically treated with a blender or grinder to obtain fine cellulose fibers, i.e., cellulose nanofibers (hereinafter also referred to as "CNF"). It is described that the CNF obtained by this method has a minor axis diameter of 10 to 50 nm and a major axis diameter of 1 μm to 10 mm. This CNF is one-fifth the weight of steel and more than five times stronger, and can be stretched up to 250 m. 2 / g, it is expected to be used as a filler for reinforcing resins and as an adsorbent.
[0004] In the production of CNF, attempts are being actively made to make the cellulose fibers in wood easier to pulverize by chemically treating them in advance and then pulverizing them by low-energy mechanical treatment using a household mixer or the like. The method of said chemical treatment is not particularly limited, but a method in which ionic functional groups are introduced into cellulose fibers to make them easier to pulverize is preferred. The introduction of ionic functional groups into cellulose fibers makes it easier for solvents to penetrate between the cellulose microfibril structures due to the osmotic effect, and the energy required for pulverizing cellulose raw materials can be significantly reduced.
[0005] The method for introducing the ionic functional group is not particularly limited, but for example, Non-Patent Document 1 discloses a method for selectively phosphorylating the surface of cellulose fine fibers using a phosphoric acid esterification treatment. Patent Document 2 discloses carboxymethylation by reacting cellulose with monochloroacetic acid or sodium monochloroacetate in a high-concentration alkaline aqueous solution. Carboxy groups may also be introduced by directly reacting cellulose with a carboxylic anhydride compound such as maleic acid or phthalic acid gasified in an autoclave.
[0006] Also reported is a method of selectively oxidizing the surface of cellulose fine fibers using 2,2,6,6-tetramethylpiperidinyl-1-oxy radical (TEMPO), a relatively stable N-oxyl compound, as a catalyst (see, for example, Patent Document 3). The oxidation reaction using TEMPO as a catalyst (TEMPO oxidation reaction) allows for environmentally friendly chemical modification that proceeds in an aqueous system at room temperature and normal pressure, and when applied to cellulose in wood, the reaction does not proceed inside the crystals, and only the alcoholic primary carbons of the cellulose molecular chains on the crystal surface can be selectively converted to carboxy groups.
[0007] The osmotic effect caused by the ionization of carboxyl groups selectively introduced to the crystal surface by TEMPO oxidation results in the production of cellulose single nanofibers (hereinafter also referred to as CSNFs) in which individual cellulose microfibril units are dispersed in a solvent. CSNFs exhibit high dispersion stability derived from the carboxyl groups on the surface. Wood-derived CSNFs obtained from wood by the TEMPO oxidation reaction are structures with a high aspect ratio, with a minor axis diameter of around 3 nm and a major axis diameter ranging from several tens of nm to several μm, and it has been reported that their aqueous dispersions and molded bodies have high transparency. Patent Document 4 describes that a laminated film obtained by coating and drying a CSNF dispersion has gas barrier properties.
[0008] Patent Document 5 describes that a dispersion in which finely divided cellulose is highly dispersed in an organic solvent can be obtained by surface modification in which an organic onium cation is arranged as a counter ion for finely divided cellulose having cationic properties.
[0009] As an example of a coating composition using finely divided cellulose, for example, Patent Document 6 describes an aqueous coating liquid containing TEMPO oxidized CNF. It is described that this aqueous coating liquid has good coatability, and by coating it on an anchor layer, a laminate having barrier properties can be obtained. Patent Document 7 discloses a coating liquid containing TEMPO-oxidized CNF, in which carbon particles are dispersed and stabilized by utilizing the entanglement and thickening properties of the high aspect ratio fibers of cellulose nanofibers, and the effect of the electric charge derived from the carboxyl groups.
[0010] On the other hand, for practical use of CNF, the solid content concentration of the obtained CNF dispersion is low, about 0.1 to 5%, which is an issue. For example, when trying to transport a fine cellulose dispersion, it is transported together with a large amount of solvent, which increases the transportation cost and significantly affects business feasibility. In addition, when used as an additive for strengthening resin, there are problems such as poor addition efficiency due to the low solid content concentration and difficulty in compounding when the solvent water is not compatible with the resin. Furthermore, when distributing in a water-containing state, there is a risk of spoilage, so measures such as refrigerated storage and preservative treatment are required, which causes an increase in costs.
[0011] However, simply removing the solvent from the microfibrillated cellulose dispersion by heat drying or other methods can result in the microfibrillated cellulose flocculating, hornifying, or forming a membrane, which can prevent the expected functionality from being stably expressed when used as an additive. Furthermore, because the solid content of CNF is low, the process of removing the solvent by drying itself requires a large amount of energy, which is also a hurdle to commercial viability.
[0012] Thus, handling CNF in a dispersion state itself has become a business challenge, and there is a strong need to provide a new method for easily handling CNF.
[0013] As a new embodiment that allows easy handling of CNF, Patent Document 8 describes a composite particle that includes a coating layer made of cellulose fibers and a polymer coated with the coating layer. In this composite particle, the cellulose fibers and the polymer are integrated, so that they can be easily separated by filtration and distributed as a powder. The redispersibility of the powder is also good. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2010-216021 A [Patent Document 2] International Publication No. 2014 / 088072 [Patent Document 3] JP 2008-001728 A [Patent Document 4] International Publication No. 2013 / 042654 [Patent Document 5] JP 2015-101694 A [Patent Document 6] Patent No. 5928339 [Patent Document 7] Patent No. 6020454 [Patent Document 8] JP 2019-38949 A [Non-patent literature]
[0015] [Non-Patent Document 1] Noguchi Y, Homma I, Matsubara Y. Complete nanofibrillation of cellulose prepared by phosphorylation. Cellulose. 2017;24:1295.10.1007 / s10570-017-1191-3 Summary of the Invention [Problem to be solved by the invention]
[0016] Although the composite particles described in Patent Document 8 are excellent as a material that exhibits the properties of CNF as described above, there is room for improvement in that the types of polymers that can be applied are limited. When composite particles are formed using inapplicable resin materials, various problems arise, such as a significant drop in yield, large variation in the particle size distribution of the obtained particles, and a small amount of CNF present on the surface of the particles, which prevents the material from fully exhibiting the CNF properties.
[0017] In view of the above circumstances, an object of the present invention is to provide a composite particle of cellulose fiber which is easy to handle and has high versatility, and a method for producing the same. [Means for solving the problem]
[0018] A first aspect of the present invention is a composite particle comprising a core particle containing at least one type of polymer, and micronized cellulose having an anionic functional group, inseparably bonded to the core particle, and disposed on the surface of the core particle. In the composite particles, an organic onium cation or an amine is bonded to at least a portion of the finely divided cellulose.
[0019] A second aspect of the present invention is a method for producing composite particles. This production method includes a first step of defibrating an anionic cellulose raw material in a solvent containing an organic onium compound or an amine to obtain a microfibrillated cellulose dispersion containing microfibrillated cellulose bonded to an organic onium cation or an amine, a second step of stabilizing a liquid core particle precursor in the microfibrillated cellulose dispersion as an emulsion, and a third step of solidifying the core particle precursor to form core particles, thereby obtaining composite particles in which the core particles are coated with microfibrillated cellulose that is inseparably bonded to the core particles. Effect of the Invention
[0020] According to the present invention, composite particles of cellulose fibers which are easy to handle and highly versatile can be provided. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic diagram of a composite particle according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing one process of the method for producing the composite particle. [Diagram 3] FIG. 2 is a diagram showing one process of the method for producing the composite particle. [Figure 4] 1 is a graph showing the results of FT-IR measurement of a micronized cellulose dispersion according to an example of the composite particle. [Diagram 5] 1 is a scanning electron microscope image of a composite particle according to an embodiment. [Figure 6] 1 is a scanning electron microscope image of a composite particle according to an embodiment. [Figure 7] 1 is a scanning electron microscope image of a composite particle according to a comparative example. [Figure 8] 1 is a scanning electron microscope image of a composite particle according to a comparative example. [Figure 9] 1 is a graph showing the particle size distribution of composite particles according to an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] An embodiment of the present invention will be described below with reference to the drawings. However, in each of the drawings described below, the same reference numerals are used to designate corresponding parts, and the description of overlapping parts will be omitted as appropriate. In addition, this embodiment is an example of a configuration for embodying the technical idea of the present invention, and the material, shape, structure, arrangement, dimensions, etc. of each part are not specified as described below. The technical idea of the present invention can be modified in various ways within the technical scope defined by the claims described in the claims.
[0023] <Composite particle 5> First, the composite particle 5 of fine cellulose / core particle according to the first embodiment of the present invention will be described. One aspect of the core particle 3 is a resin, which is also called a polymer. 1 shows a schematic diagram of a composite particle 5. The composite particle 5 includes a core particle 3 and finely divided cellulose 1 located on the surface of the core particle 3. In the composite particle 5, the finely divided cellulose 1 forms a finely divided cellulose layer 10, and is bonded to the core particle 3 in an inseparable state. At least a portion of the fine cellulose 1 is bound to an organic onium cation or an amine 7a as a counter cation. The ionized state of the organic onium compound is referred to as an organic onium ion or an organic onium cation. The amine referred to here is a state in which a part or all of the amine is ionized and contains an ammonium ion. Hereinafter, either the organic onium compound or the amine, or the organic onium cation or the ammonium ion, will also be referred to as "organic onium compound / amine" or "organic onium cation (or organic onium ion) / ammonium ion", respectively.
[0024] The composite particles 5 are obtained by solidifying an O / W type Pickering emulsion using fine cellulose 1 and a liquid core particle precursor 2 (hereinafter simply referred to as "droplets") of the emulsion oil droplets (oil phase, oil particles, dispersed phase).
[0025] The core particle precursor 2 can be solidified by various methods. For example, a polymerization granulation method (emulsion polymerization method, suspension polymerization method, seed polymerization method, radiation polymerization method, etc.) in which particles are formed during polymerization using a monomer having a polymerizable functional group (hereinafter also referred to as a "polymerizable monomer") as the core particle precursor 2, and a dispersion granulation method (spray drying method, in-liquid curing method, solvent evaporation method, phase separation method, solvent dispersion cooling method, etc.) in which particles are formed from a polymer solution in fine droplets can be mentioned. In this embodiment, "solidification of the core particle precursor" is a concept that includes all of: (1) polymerizing the polymerizable monomer droplets, (2) solidifying the polymer droplets, and (3) solidifying the polymerizable monomer droplets and the polymer droplets.
[0026] The O / W type Pickering emulsion is stabilized by the adsorption of the micronized cellulose 1 to the interface of the core particle precursor 2 dispersed in the hydrophilic solvent of the continuous phase. By solidifying the core particle precursor 2 inside the emulsion while maintaining the stabilized state, composite particles 5 can be produced using the emulsion as a template. Here, the "stabilized state of the emulsion" means a state in which the droplet size of the emulsion does not change even if it is left to stand for a long period of time (for example, 12 hours). If the emulsion is unstable, some of the droplets will coalesce with each other over time, causing the particle size distribution of the droplets to shift to a larger size than at the beginning, causing variation in the particle size distribution, and in some cases causing separation of the oil phase and the water phase. As a result, the composite particles obtained will be non-uniform.
[0027] The mechanism by which fine cellulose 1 is adsorbed to the droplet interface and stabilizes an O / W Pickering emulsion is thought to be related to the effect of a decrease in interfacial energy due to adsorption. Fine cellulose 1, which is a finely divided solid particle on the submicron order, is adsorbed to the droplet interface by physical forces and forms a cellulose barrier against the aqueous phase. Once adsorbed and an interface is formed, a larger energy is required for desorption, and the emulsion structure is stabilized. Furthermore, it is speculated that the microfibrillated cellulose 1 is amphiphilic, and the hydrophobic side of the microfibrillated cellulose 1 is adsorbed to the hydrophobic droplets, and the hydrophilic side of the microfibrillated cellulose 1 faces the dispersion solvent, improving the stabilization of the droplet interface. The adsorption force at this interface depends on both the affinity of the solid particles to the oil phase and the water phase, that is, the affinity of the microfibrillated cellulose 1 to the core particle precursor and the affinity of the microfibrillated cellulose 1 to the dispersion solvent.
[0028] In this embodiment, the affinity of the fine cellulose 1 for droplets is increased and the adsorptive power is improved by imparting hydrophobicity to a part of the fine cellulose 1. As a method for imparting hydrophobicity, a method in which an organic onium compound / amine 7 is used for the fine cellulose 1 having an anionic functional group to make the counter ion an organic onium ion / ammonium ion 7a is preferred, because the effect of imparting hydrophobicity is high and it is advantageous in terms of process cost. The stability of the emulsion is improved by producing the composite particles 5 using the partially hydrophobized fine cellulose 1. As a result, the types of applicable core particle precursor materials are significantly increased, and a variety of composite particles 5 that can meet the required specifications according to applications, etc. can be produced.
[0029] In this embodiment, the term "inseparable" indicating the bonded state between the core particle 3 and the micronized cellulose 1 means that the micronized cellulose 1 and the core particle 3 do not separate, and the coating state of the core particle 3 with the micronized cellulose 1 is maintained, even after the operation of purifying and washing the composite particle 5 by centrifuging the dispersion liquid containing the composite particle 5 to remove the supernatant and then redispersing it by adding a solvent, or the operation of repeatedly washing with a solvent by filtration and washing using a membrane filter is repeated. The state of coverage of the core particle 3 with the finely divided cellulose 1 can be confirmed by observing the surface of the composite particle 5 with a scanning electron microscope (SEM). Although the detailed mechanism by which the finely divided cellulose 1 and the core particle 3 are inseparably bonded has not been clarified, the composite particle 5 is produced using an O / W type emulsion stabilized by the finely divided cellulose 1 as a template. Therefore, when the droplets inside the emulsion are solidified while in contact with the finely divided cellulose 1, a part of the finely divided cellulose 1 is fixed while remaining in the droplet, and it is considered that the core particle 3 and the finely divided cellulose 1 are ultimately inseparably bonded. O / W type emulsions are also called oil-in-water emulsions, in which water is the continuous phase and oil is dispersed as oil droplets (oil particles).
[0030] One of the characteristics of the composite particle 5 is that it has a nearly spherical shape derived from the O / W emulsion, since it is produced using as a template an O / W emulsion stabilized by the fine cellulose 1. In a typical composite particle 5, a fine cellulose layer 10 made of the fine cellulose 1 is formed on the surface of a spherical core particle 3 with a relatively uniform thickness. The average thickness of the microfibrillated cellulose layer 10 is obtained by cutting the composite particles 5 fixed in an embedding resin with a microtome, observing them with an SEM, randomly measuring the thickness of the microfibrillated cellulose layer 10 in the cross-sectional image of the composite particle 5 in the image at 100 points on the image, and calculating the arithmetic average value. The uniform thickness of the fine cellulose layer 10 is also one of the features of the composite particle 5. The coefficient of variation of the thickness value of the fine cellulose layer 10 (standard deviation of 30 points randomly selected from the above-mentioned 100 points) is preferably 0.5 or less, and more preferably 0.4 or less.
[0031] The fine cellulose 1 in this embodiment is not particularly limited, but has anionic functional groups on the crystal surface, and the content of the anionic functional groups is preferably 0.1 mmol or more and 5.0 mmol or less per 1 g of cellulose.
[0032] Furthermore, the fine cellulose 1 preferably has a fibrous shape derived from a microfibril structure. Specifically, the fine cellulose 1 is fibrous, and preferably has a number average minor axis diameter of 1 nm to 1000 nm, a number average major axis diameter of 50 nm or more, and a number average major axis diameter of 5 times or more the number average minor axis diameter. The crystal structure of the fine cellulose 1 is preferably cellulose type I.
[0033] <Method of Manufacturing Composite Particle 5> A method for producing the composite particle 5 of this embodiment will be described. The method for producing the composite particle of this embodiment includes a step (first step) of obtaining a microfibrillated cellulose dispersion by defibrating an anionic cellulose raw material 6 in a solvent containing an organic onium compound / amine 7, a step (second step) of stabilizing the liquid core particle precursor 2 as an emulsion in the microfibrillated cellulose dispersion, and a step (third step) of solidifying the core particle precursor 2 to obtain composite particles coated with microfibrillated cellulose 1.
[0034] The composite particles 5 obtained by the above manufacturing method are obtained as a dispersion. When the solvent is removed from the dispersion, a dry solid of the composite particles 5 that is easy to handle is obtained. The method of removing the solvent is not particularly limited, and examples include a method of removing the solvent by centrifugation or filtration, and a method of removing the solvent by evaporating it in an oven or the like. In this case, the dry solid of the composite particles 5 obtained is not in the form of a film or aggregate, but is a fine powder. Although the reason for this is unclear, in the case of a dispersion containing the composite particles 5, since the composite particles are substantially spherical composite particles with the fine cellulose 1 fixed to the surface, one of the reasons is thought to be that the fine cellulose 1 does not aggregate with each other even when the solvent is removed, but only comes into point contact with adjacent composite particles. Since the composite particles 5 do not aggregate, it is easy to redisperse the composite particles 5 obtained as a dry powder in a solvent, and even after redispersion, the dispersion stability derived from the fine cellulose 1 bound to the surface is exhibited.
[0035] The dry powder of composite particle 5 is a dry solid that contains almost no solvent and is further characterized by being redispersible in a solvent, and specifically, the solid content can be 80% or more, and can also be 90% or more, and can even be 95% or more. Since the dispersion of the composite particles 5 can be almost completely free of the solvent, it has favorable effects in terms of reducing transportation costs, preventing spoilage, improving the additive rate, and improving the efficiency of kneading with the resin. Even if the solid content is increased to 80% or more by drying, the fine cellulose 1 is prone to hygroscopicity, and may adsorb moisture in the air and reduce the solid content over time, resulting in a possibility of it becoming 80% or less during storage. However, considering the technical concept of the present invention, which is characterized in that the composite particles 5 can be easily obtained as a dry powder and can be further redispersed, it should be said that any dry solid obtained through a process in which the solid content of the dry powder containing the composite particles 5 is increased to 80% or more is within the technical scope of the present invention. Each step of the manufacturing method will now be described in detail.
[0036] (1st step) The first step in this embodiment is shown in FIG. The first step is a step of defibrating an anionic cellulose raw material 6 in a solvent containing an organic onium compound / amine 7 to obtain a microfibrillated cellulose dispersion. First, as shown in Fig. 2, a cellulose raw material 6 having various anionic properties is mixed with an organic onium compound / amine 7. As a result, an organic onium cation / ammonium ion 7a contained in the organic onium compound / amine 7 bonds with the cellulose raw material 6, imparting hydrophobicity to a part of the cellulose raw material 6.
[0037] The cellulose raw material 6 having anionic properties may form a salt with a cationic substance such as a metal ion as a counter ion. However, it is preferable that the cellulose raw material 6 does not contain a cationic substance, because the production of by-products can be suppressed and the hydrophobization effect is excellent when the cationic substance is not contained. The content of cationic substances in the cellulose raw material 6 can be examined by various analytical methods. For example, simple methods include an EPMA method using an electron probe microanalyzer and elemental analysis by X-ray fluorescence analysis. A method for removing cationic substances from the anionic cellulose raw material 6 is a purification method in which the cellulose raw material 6 is repeatedly washed under acidic conditions and then repeatedly washed with pure water.
[0038] The amount of the organic ammonium compound / amine 7 bound is preferably 0.8 equivalents or more and 2 equivalents or less relative to the anionic functional group contained in the cellulose raw material 6. In particular, if the amount of bound is 1 equivalent or more and 1.8 equivalents or less, it is more preferable since it is not necessary to add a large amount of the organic onium compound / amine 7. Even if the amount of bound organic onium compound / amine 7 is less than 0.8 equivalents, it is possible to disperse the cellulose raw material 6 to some extent, but the dispersion treatment requires a long time and high energy, and the fiber diameter of the obtained fibers becomes large and the homogeneity decreases. On the other hand, if the amount of bound organic onium compound / amine 7 exceeds 2 equivalents, the excessive addition of the organic onium compound / amine 7 may cause decomposition of the cellulose raw material 6 or a decrease in affinity for the dispersion medium, which is not preferable. The organic onium compound / amine 7 may be of one type or a mixture of two or more types. In particular, organic oniums or amines having different structures of hydroxyl groups or hydrocarbon groups may be used. Alternatively, the hydrocarbon group may be linear or branched.
[0039] Next, the cellulose raw material 6 to which the organic onium compound / amine 7 is bonded is dispersed in a solvent to prepare a suspension of the hydrophobic cellulose raw material 6. Water is suitable as the solvent, and it is preferable that the solvent contains 50% or more of water. If the proportion of water in the solvent is 50% or less, the stability of the emulsion of the liquid core particle precursor is hindered in the second step described below. The ratio of the cellulose raw material 6 in the dispersion is preferably 0.1% or more and less than 10%. If it is less than 0.1%, the amount of solvent becomes excessive, which impairs productivity, and if it is 10% or more, the suspension rapidly thickens as the cellulose raw material 6 is defibrated, which makes it difficult to perform a uniform defibration process, which is also not preferred.
[0040] The pH of the suspension is preferably 4 or more and 12 or less. In particular, when the suspension is made alkaline with a pH of 7 or more and 12 or less, the anionic functional groups of the cellulose raw material 6 are ionized. This makes it easier for the solvent to penetrate into the cellulose raw material 6 due to the osmotic pressure effect, and the pulverization of the cellulose raw material 6 is facilitated. When the pH is less than 4, the cellulose raw material 6 can be dispersed by a mechanical dispersion treatment, but the same phenomenon occurs as when the amount of the organic onium compound / amine 7 added is too small, and the homogeneity of the pulverized cellulose 1 in the dispersion liquid decreases. On the other hand, when the pH exceeds 12, the cellulose raw material 6 having anionic properties undergoes a peeling reaction or is reduced in molecular weight due to alkaline hydrolysis during the dispersion treatment, and the yellowing of the dispersion liquid is promoted due to the formation of terminal aldehydes and double bonds, which is not preferable.
[0041] The organic onium compound in this embodiment has a cation structure represented by the structural formula (1).
[0042] [ka]
[0043] In structural formula (1), M is any one of a nitrogen atom, a phosphorus atom, a hydrogen atom, and a sulfur atom, and R1, R2, R3, and R4 are any one of a hydrogen atom, a hydrocarbon group, and a hydrocarbon group containing a hetero atom. For example, when M is a nitrogen atom and R1, R2, R3 and R4 are all hydrogen atoms, the organic onium compound is ammonia. When three of R1, R2, R3 and R4 are hydrogen atoms, the organic onium compound is a primary amine, when two are hydrogen atoms, the organic onium compound is a secondary amine, when one is hydrogen atoms, the organic onium compound is a tertiary amine, and when none is hydrogen atoms, the organic onium compound is a quaternary amine, and all of these are organic onium compounds according to the present embodiment. Examples of the hydrocarbon group containing a heteroatom include an alkyl group, an alkylene group, an oxyalkylene group, an aralkyl group, an aryl group, and an aromatic group. R1, R2, R3 and R4 may form a ring.
[0044] The counter ion of the cationic structure of the organic onium compound is not particularly limited, but taking into consideration the adverse effects of contamination with metal ions and dispersibility in a dispersion medium, the counter ion is preferably a hydroxide ion. In the first step, in addition to the organic onium compound, an inorganic alkali including a metal salt such as an alkali metal or an alkaline earth metal may be added.
[0045] In this embodiment, the primary amine, secondary amine, and tertiary amine have the structures shown in the following structural formulas (2), (3), and (4), respectively. When these are ionized to become ammonium ions, the structures become (2)', (3)', and (4)', respectively.
[0046] [ka]
[0047] In the above structural formula, R1 to R6 are either a hydrocarbon group or a hydrocarbon group containing a hetero atom.
[0048] Examples of primary amines, secondary amines, and tertiary amines include methylamine, ethylamine, propylamine, butylamine, n-octylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, hexylamine, 2-ethylhexylamine, dihexylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trioctylamine, trihexylamine, dioctylamine, dodecylamine, stearylamine, and oleylamine.
[0049] The suspension obtained by using the anionic cellulose raw material 6 and the organic onium compound / amine 7 can be dispersed with less energy and in a shorter time than when using inorganic alkali with a metal ion as a counter ion, and the final dispersion has high homogeneity. This is thought to be because the organic onium compound / amine 7 has a larger ionic diameter of the counter ion of the anionic part of the cellulose raw material 6, and therefore has a greater effect of separating the fine cellulose fibers from each other in the dispersion medium. Furthermore, when the organic onium compound / amine 7 is contained in the dispersion, the viscosity and thixotropy of the dispersion can be reduced compared to inorganic alkali, which is advantageous in terms of ease of dispersion and subsequent handling. Furthermore, the fine cellulose 1 that interacts with the organic onium compound / amine 7 through ionic bonds is reduced in hydrophilicity due to steric repulsion or hydrophobic action based on the organic onium ion / ammonium ion 7a. As a result, in the second step described below, the affinity of the liquid core particle precursor 2 to the emulsion droplets is increased, and the stability of the droplets is improved.
[0050] The suspension is then subjected to a physical defibration treatment to pulverize the cellulose raw material 6. The method of the physical defibration treatment is not particularly limited, and examples of the method include mechanical treatments such as a high-pressure homogenizer, an ultra-high-pressure homogenizer, a ball mill, a roll mill, a cutter mill, a planetary mill, a jet mill, an attritor, a grinder, a juicer mixer, a homomixer, an ultrasonic homogenizer, a nanogenizer, and underwater counter-collision. By performing the physical defibration treatment, the cellulose raw material 6 in the suspension is pulverized, and a dispersion of the pulverized cellulose 1 in which at least one side of the structure is pulverized to the order of nanometers can be obtained. By changing the time and number of times of the physical defibration treatment, the number average minor axis diameter and the number average major axis diameter of the pulverized cellulose 1 contained in the dispersion can be adjusted.
[0051] In this manner, a dispersion 4 of the fine cellulose 1 shown in Fig. 2 is obtained. The fine cellulose 1 is finely divided to such an extent that at least one side of the structure is on the order of nanometers. Since the fine cellulose 1 has a fiber shape derived from a microfibril structure, the fine cellulose 1 used in the manufacturing method of this embodiment preferably has a fiber shape within the range shown below. That is, the number average minor axis diameter of the fibrous fine cellulose 1 may be 1 nm or more and 1000 nm or less, preferably 2 nm or more and 500 nm or less. Here, if the number average minor axis diameter is less than 1 nm, a highly crystalline rigid fine cellulose fiber structure cannot be obtained, and emulsion stabilization and polymerization reaction using the emulsion as a template cannot be performed. On the other hand, if the number average minor axis diameter exceeds 1000 nm, the size becomes too large to stabilize the emulsion, making it difficult to control the size and shape of the obtained composite particles 5. Although there is no particular limitation on the number average major axis diameter of the fine cellulose 1, it is preferably 5 times or more the number average minor axis diameter. If the number average major axis diameter is less than 5 times the number average minor axis diameter, it is not preferable because the size and shape of the composite particles 5 cannot be sufficiently controlled. The number average minor axis diameter of the fine cellulose 1 is determined by measuring the minor axis diameters (minimum diameters) of 100 fibers by observation with a transmission electron microscope and an atomic force microscope, and taking the average value thereof. The number average major axis diameter of the fine cellulose 1 is determined by measuring the major axis diameters (maximum diameters) of 100 fibers by observation with a transmission electron microscope and an atomic force microscope, and taking the average value thereof. In Dispersion 4, organic onium compound / amine 7 is bonded to fine cellulose 1, and exhibits good dispersion. Dispersion 4 can be used as a stabilizer for O / W emulsions in the subsequent step, either as is or after dilution, concentration, etc.
[0052] The type and crystal structure of the cellulose constituting the fine cellulose 1 are not particularly limited. Specifically, as a raw material consisting of cellulose type I crystals, for example, in addition to wood-based natural cellulose, non-wood-based natural cellulose such as cotton linter, bamboo, hemp, bagasse, kenaf, bacterial cellulose, sea squirt cellulose, and valonia cellulose can be used. Furthermore, regenerated cellulose represented by rayon fiber and cupra fiber consisting of cellulose type II crystals can also be used. In view of ease of material procurement, it is preferable to use wood-based natural cellulose as the raw material. The wood-based natural cellulose is not particularly limited, and can be one generally used for the production of cellulose nanofibers, such as softwood pulp, hardwood pulp, and waste paper pulp. Softwood pulp is preferable in view of ease of purification and fineness. Furthermore, it is preferable that the cellulose raw material 6 is chemically modified. More specifically, it is preferable that anionic functional groups are introduced to the crystal surfaces of the cellulose raw material 6. This is because the introduction of anionic functional groups to the crystal surfaces of the cellulose raw material 6 makes it easier for the solvent to penetrate between the cellulose crystals due to the osmotic pressure effect, facilitating the pulverization of the cellulose raw material 6.
[0053] The type and method of the anionic functional group to be introduced to the cellulose crystal surface are not particularly limited, but a carboxy group or a phosphate group is preferred. The carboxy group is preferred because it can be easily selectively introduced to the cellulose crystal surface.
[0054] The method of introducing a carboxy group onto the crystal surface of cellulose is not particularly limited. Specifically, for example, carboxymethylation may be carried out by reacting cellulose with monochloroacetic acid or sodium monochloroacetate in a high-concentration aqueous alkali solution. Alternatively, carboxy groups may be introduced by directly reacting cellulose with a carboxylic anhydride compound such as maleic acid or phthalic acid gasified in an autoclave. Furthermore, a method using a co-oxidant in the presence of an N-oxyl compound such as TEMPO, which has high selectivity for the oxidation of alcoholic primary carbon, while maintaining the structure as much as possible under relatively mild aqueous conditions, may be used. Oxidation using an N-oxyl compound is more preferable for selectivity of the carboxy group introduction site and reduction of environmental load.
[0055] Here, examples of the N-oxyl compound include TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxy radical), 2,2,6,6-tetramethyl-4-hydroxypiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-N-oxyl, 4-ethoxy-2,2,6,6-tetramethylpiperidine-N-oxyl, and 4-acetamido-2,2,6,6-tetramethylpiperidine-N-oxyl. Among these, TEMPO, which has high reactivity, is preferred. The amount of the N-oxyl compound used may be the amount used as a catalyst, and is not particularly limited. Usually, it is about 0.01 to 5.0% by mass based on the solid content of the wood-based natural cellulose to be oxidized.
[0056] An example of an oxidation method using an N-oxyl compound is a method in which wood-based natural cellulose is dispersed in water and oxidized in the presence of an N-oxyl compound. In this case, it is preferable to use a co-oxidizing agent together with the N-oxyl compound. In this case, the N-oxyl compound is sequentially oxidized by the co-oxidizing agent in the reaction system to generate an oxoammonium salt, and the cellulose is oxidized by the oxoammonium salt. This oxidation treatment allows the oxidation reaction to proceed smoothly even under mild conditions, improving the efficiency of introducing a carboxyl group. When the oxidation treatment is performed under mild conditions, the crystal structure of cellulose is easily maintained.
[0057] As the co-oxidizing agent, any oxidizing agent can be used as long as it can promote the oxidation reaction, such as halogen, hypohalous acid, halo-ous acid, perhalogen acid, or their salts, halogen oxide, nitrogen oxide, peroxide, etc. Sodium hypochlorite is preferred in view of availability and reactivity. The amount of the co-oxidizing agent used is not particularly limited, and may be an amount that can promote the oxidation reaction. Usually, it is about 1 to 200 mass% based on the solid content of the wood-based natural cellulose to be oxidized.
[0058] In addition, at least one compound selected from the group consisting of bromides and iodides may be used in combination with the N-oxyl compound and the co-oxidizing agent. This allows the oxidation reaction to proceed smoothly, and improves the efficiency of introducing a carboxyl group. As such a compound, sodium bromide or lithium bromide is preferred, and sodium bromide is more preferred in terms of cost and stability. The amount of the compound used is not particularly limited, and may be an amount that can promote the oxidation reaction. Usually, it is about 1 to 50% by mass based on the solid content of the wood-based natural cellulose to be oxidized.
[0059] The reaction temperature of the oxidation reaction is preferably 4 to 80° C., more preferably 10 to 70° C. If it is less than 4° C., the reactivity of the reagent decreases and the reaction time becomes longer. If it is more than 80° C., side reactions are promoted, the sample becomes low molecular weight, and the highly crystalline rigid fine cellulose fiber structure collapses, making it impossible to use it as a stabilizer for O / W type emulsions.
[0060] The reaction time for the oxidation treatment can be appropriately set in consideration of the reaction temperature, the desired amount of carboxy groups, etc., and is not particularly limited, but is usually about 10 minutes to 5 hours.
[0061] The pH of the reaction system during the oxidation reaction is not particularly limited, but is preferably 9 to 11. When the pH is 9 or more, the reaction can proceed efficiently. When the pH exceeds 11, a side reaction may proceed, which may accelerate the decomposition of the sample. In addition, in the oxidation treatment, as the oxidation proceeds, carboxyl groups are generated, which lowers the pH in the system, so it is preferable to keep the pH of the reaction system at 9 to 11 during the oxidation treatment. As a method for keeping the pH of the reaction system at 9 to 11, a method of adding an alkaline aqueous solution in response to the decrease in pH can be mentioned.
[0062] Examples of the aqueous alkali solution include aqueous solutions of organic onium compounds such as an aqueous sodium hydroxide solution, an aqueous lithium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous ammonia solution, an aqueous tetramethylammonium hydroxide solution, an aqueous tetraethylammonium hydroxide solution, an aqueous tetrabutylammonium hydroxide solution, and an aqueous benzyltrimethylammonium hydroxide solution. In terms of cost, an aqueous sodium hydroxide solution is preferred.
[0063] The oxidation reaction by the N-oxyl compound can be stopped by adding an alcohol to the reaction system. In this case, it is preferable to keep the pH of the reaction system within the above range. As the alcohol to be added, low molecular weight alcohols such as methanol, ethanol, and propanol are preferable in order to quickly terminate the reaction, and ethanol is particularly preferable in view of the safety of by-products generated by the reaction.
[0064] The reaction solution after the oxidation treatment may be directly subjected to the microparticulation step, but it is preferable to recover the oxidized cellulose contained in the reaction solution and wash it with a washing solution in order to remove catalysts such as N-oxyl compounds, impurities, etc. The recovery of the oxidized cellulose can be carried out by a known method such as filtration using a glass filter or a nylon mesh with a pore size of 20 μm. Pure water is preferable as the washing solution used to wash the oxidized cellulose.
[0065] When the obtained TEMPO-oxidized cellulose is subjected to defibration treatment, cellulose single nanofibers (CSNF) with a uniform fiber width of 3 nm are obtained. When CSNF is used as the raw material for the micronized cellulose 1 of the composite particle 5, the particle size of the obtained O / W type emulsion tends to be uniform due to its uniform structure.
[0066] As described above, the CSNF used in this embodiment can be obtained by a process of oxidizing the cellulose raw material and a process of pulverizing and dispersing it. The content of the carboxyl group introduced into the CSNF is preferably 0.1 mmol / g or more and 5.0 mmol / g or less, and more preferably 0.5 mmol / g or more and 2.0 mmol / g or less. Here, if the amount of the carboxyl group is less than 0.1 mmol / g, the solvent does not penetrate between the cellulose microfibrils due to the osmotic pressure effect, so it is difficult to pulverize the cellulose and disperse it uniformly. If the amount of the carboxyl group exceeds 5.0 mmol / g, the cellulose microfibrils are depolymerized due to a side reaction accompanying the chemical treatment, so that a highly crystalline rigid pulverized cellulose fiber structure cannot be obtained, and the cellulose cannot be used as a stabilizer for O / W type emulsions.
[0067] The dispersion liquid 4 may contain other components other than cellulose and the components used for adjusting the pH, as necessary, within a range that does not impair the effects of the present invention. The other components are not particularly limited and can be appropriately selected from known additives depending on the application of the composite particles 5. Specifically, organic metal compounds such as alkoxysilanes or hydrolysates thereof, inorganic layered compounds, inorganic acicular minerals, defoamers, inorganic particles, organic particles, lubricants, antioxidants, antistatic agents, UV absorbers, stabilizers, magnetic powders, alignment promoters, plasticizers, crosslinkers, magnetic materials, pharmaceuticals, pesticides, fragrances, adhesives, enzymes, pigments, dyes, deodorants, metals, metal oxides, inorganic oxides, etc. may be mentioned.
[0068] (Second process) The second step is a step of coating the surfaces of the liquid core particle precursors 2 with the fine cellulose 1 in the dispersion 4 of the fine cellulose 1 obtained in the first step, thereby stabilizing the core particle precursors as an emulsion.
[0069] Specifically, this is a process in which liquid core particle precursor 2 is added to the dispersion liquid 4 obtained in the first step, the core particle precursor 2 is dispersed as droplets in the dispersion liquid 4, and the surfaces of the droplets are coated with micronized cellulose 1, thereby producing an O / W type emulsion stabilized by a micronized cellulose layer 10, as shown on the left side of Figure 3.
[0070] The method for producing the O / W emulsion is not particularly limited, and may be a general emulsification treatment, such as various homogenizer treatments or mechanical stirring treatments, and specific examples of such mechanical treatments include high-pressure homogenizers, ultra-high-pressure homogenizers, universal homogenizers, ball mills, roll mills, cutter mills, planetary mills, jet mills, attritors, grinders, juicer mixers, homomixers, ultrasonic homogenizers, nanogenizers, underwater counter-impingement, paint shakers, etc. A combination of multiple mechanical treatments may also be used.
[0071] For example, when an ultrasonic homogenizer is used, a polymerizable monomer is added to the fine cellulose dispersion obtained in the first step to prepare a mixed solvent, and the tip of the ultrasonic homogenizer is inserted into the mixed solvent to perform ultrasonic treatment. The treatment conditions for the ultrasonic homogenizer are not particularly limited, but for example, a frequency of 20 kHz or more and an output of 10 W / cm are generally used. 2 The above is typical. There is no particular restriction on the treatment time, but it is usually about 10 seconds to 1 hour.
[0072] The ultrasonic treatment causes droplets of the core particle precursor 2 to disperse in the dispersion liquid 4, and emulsification proceeds. Furthermore, the fine cellulose 1 is selectively adsorbed to the liquid / liquid interface between the droplets and the dispersion liquid 4, and the droplets are covered with the fine cellulose 1 to form a stable structure as an O / W type emulsion. An emulsion stabilized by the adsorption of a solid substance to the liquid / liquid interface in this way is academically called a "Pickering emulsion." As mentioned above, the mechanism by which Pickering emulsion is formed by fine cellulose fibers is not clear, but cellulose exhibits amphiphilicity due to its molecular structure having hydrophilic sites derived from hydroxyl groups and hydrophobic sites derived from hydrocarbon groups, and it is considered that cellulose is adsorbed to the liquid / liquid interface between the hydrophobic monomer and the hydrophilic solvent due to its amphiphilicity.
[0073] The O / W emulsion structure can be confirmed by observation with an optical microscope. The particle size of the O / W emulsion is not particularly limited, but is usually about 0.1 μm to 1000 μm.
[0074] In the O / W emulsion structure, the thickness of the fine cellulose layer 10 formed on the surface of the droplets is not particularly limited, but is usually about 3 nm to 1000 nm. The thickness of the fine cellulose layer 10 can be measured using, for example, a cryo-TEM.
[0075] The material of the liquid core particle precursor 2 that can be used in the second step is not particularly limited as long as it is insoluble in water and is one of the following: (1) a monomer (polymerizable monomer) having a polymerizable functional group that can form a solid polymer by a polymerization reaction; (2) a thermoplastic polymer that melts into a liquid state when heated and undergoes a phase transition to become solid at room temperature; and (3) a non-curable polymer that dissolves into a liquid state in a solvent and becomes solid at room temperature when the solvent is removed.
[0076] Regarding (1), the polymerizable monomer has at least one polymerizable functional group. A polymerizable monomer having one polymerizable functional group is also called a monofunctional monomer. A polymerizable monomer having two or more polymerizable functional groups is also called a polyfunctional monomer. The type of polymerizable monomer is not particularly limited, and examples thereof include (meth)acrylic monomers and vinyl monomers. It is also possible to use a polymerizable monomer having an epoxy group or a cyclic ether structure such as an oxetane structure (e.g., ε-caprolactone, etc.). The term "(meth)acrylate" is meant to include both "acrylate" and "methacrylate."
[0077] Examples of monofunctional (meth)acrylic monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth). ) acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphate (meth)acrylate, ethylene oxide modified phosphate (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, proline Pyrene oxide modified phenoxy (meth)acrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrohydrogen phthalate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen phthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate,Examples of the mono(meth)acrylate include adamantane derivative mono(meth)acrylates such as adamantyl acrylate having a monovalent mono(meth)acrylate derived from 2-adamantane and adamantanediol.
[0078] Examples of bifunctional (meth)acrylic monomers include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0079] Examples of the trifunctional or higher (meth)acrylic monomer include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethylisocyanurate tri(meth)acrylate, and glycerin tri(meth)acrylate; trifunctional (meth)acrylate compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate. Examples of the (meth)acrylate include polyfunctional (meth)acrylate compounds having three or more functional groups, such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate, as well as polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone.
[0080] As the monofunctional vinyl monomer, for example, a vinyl ether type, a vinyl ester type, an aromatic vinyl type, particularly styrene and a styrene type monomer, etc., which are liquids that are incompatible with water at room temperature, are preferable. Examples of the (meth)acrylate among the monofunctional vinyl monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, alkyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, allyl (meth)acrylate, diethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, heptafluorodecyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and tricyclodecanyl (meth)acrylate. Examples of monofunctional aromatic vinyl monomers include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, isopropenyltoluene, isobutyltoluene, tert-butylstyrene, vinylnaphthalene, vinylbiphenyl, and 1,1-diphenylethylene.
[0081] The polyfunctional vinyl monomer may be a polyfunctional monomer having an unsaturated bond such as divinylbenzene, etc. A liquid that is incompatible with water at room temperature is preferred. Specific examples of polyfunctional vinyl monomers include: (1) divinyls such as divinylbenzene, 1,2,4-trivinylbenzene, and 1,3,5-trivinylbenzene; (2) dimethacrylates such as ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, 1,3-propylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, 1,6-hexamethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, dipropylene glycol dimethacrylate, polypropylene glycol dimethacrylate, and 2,2-bis(4-methacryloxydiethoxyphenyl)propane; (3) trimethacrylates such as trimethylolpropane trimethacrylate and triethylolethane trimethacrylate; (4) ethylene glycol diacrylate, diethylene glycol dimethacrylate, and diethylene glycol dimethacrylate; diacrylates such as aryl diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, 1,3-dipropylene glycol diacrylate, 1,4-dibutylene glycol diacrylate, 1,6-hexylene glycol diacrylate, neopentyl glycol diacrylate, dipropylene glycol diacrylate, polypropylene glycol diacrylate, 2,2-bis(4-acryloxypropoxyphenyl)propane, 2,2-bis(4-acryloxydiethoxyphenyl)propane, (5) triacrylates such as trimethylolpropane triacrylate, triethylolethane triacrylate, (6) tetraacrylates such as tetramethylolmethane tetraacrylate, and (7) others, for example, tetramethylene bis(ethyl fumarate), hexamethylene bis(acrylamide), triallyl cyanurate, and triallyl isocyanurate. For example, specific examples of functional styrene monomers include divinylbenzene, trivinylbenzene, divinyltoluene, divinylnaphthalene, divinylxylene, divinylbiphenyl, bis(vinylphenyl)methane, bis(vinylphenyl)ethane, bis(vinylphenyl)propane, and bis(vinylphenyl)butane.
[0082] In recent years, in consideration of the environment, there has been a strong demand for biodegradable powders that can be decomposed by microorganisms in nature after use and ultimately turn into water and carbon dioxide. Biodegradable materials can be used for the core particle 3 of this embodiment. There are no particular limitations on the biodegradable material as long as it is biodegradable and insoluble in water, and specific examples include cellulose acetate derivatives such as cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate, polysaccharides such as chitin and chitosan, polylactic acids such as polylactic acid and copolymers of lactic acid and other hydroxycarboxylic acids, dibasic acid polyesters such as polybutylene succinate, polyethylene succinate, and polybutylene adipate, polycaprolactones such as copolymers of caprolactone and hydroxycarboxylic acids, polyhydroxybutyrates such as copolymers of polyhydroxybutyrate and hydroxycarboxylic acids, aliphatic polyesters such as copolymers of polyhydroxybutyrate and other hydroxycarboxylic acids, polyamino acids, polyester polycarbonates, and natural resins such as rosin. These compounds can be used alone or in combination of two or more.
[0083] In addition to these, polyether resins, polyester resins, polyurethane resins, epoxy resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, and the like having at least one polymerizable functional group can also be used, and the material is not particularly limited. The above-mentioned various polymerizable monomers may be used alone or in combination of two or more kinds.
[0084] Regarding the above (2), the thermoplastic polymer preferably has a melting point of 40°C or more and 80°C or less. If the melting point is lower than 40°C, it is difficult to maintain the shape as a solid at room temperature, and the use environment is extremely limited, which is not preferable. On the other hand, if the melting point exceeds 80°C, it is difficult to maintain the molten state in the microfibrillated cellulose dispersion in the manufacturing process, which is not preferable. More preferably, the melting point is 45°C or more and 75°C or less. In addition, it is preferable that the melt flow rate (MFR) at or above the melting point is 10 or more. If the MFR is less than 10, it is not preferable because a large amount of emulsification energy is required in the above-mentioned emulsification treatment.
[0085] Regarding the above (3), the non-curable polymer is one that dissolves in a solvent other than water and has a liquid state. Here, the solvent that dissolves the non-curable polymer preferably has a water solubility of 20 g or more and 2000 g or less per 1 L of water at 20°C. If it is less than 20 g, the affinity between the droplets containing the solvent and the fine cellulose 1 is low, and the emulsion stabilization effect of the fine cellulose 1 decreases. On the other hand, if it is more than 2000 g, the diffusion speed of the solvent in the fine cellulose dispersion is high, so that the droplets cannot maintain their shape. As a result, the droplet covering effect of the fine cellulose 1 is impaired.
[0086] The thermoplastic polymer and the non-curable polymer are not limited in material as long as the function of the present embodiment is not impaired. For example, the above-mentioned various monofunctional monomers, polymerizable monomers having a cyclic ether structure such as an epoxy group or an oxetane structure, or polyether resins, polyester resins, polyurethane resins, epoxy resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, etc. can be used.
[0087] The weight ratio of the dispersion liquid 4 and the liquid core particle precursor 2 in the second step is not particularly limited, but it is preferable that the amount of the core particle precursor 2 is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the dispersion liquid 4. If the amount of the core particle precursor 2 is 1 part by mass or less, the yield of the composite particles 5 decreases, which is not preferable, and if it exceeds 50 parts by mass, it becomes difficult to uniformly coat the droplets with the micronized cellulose 1, which is also not preferable.
[0088] A polymerization initiator may be contained in advance when a polymerizable monomer is used as the liquid core particle precursor 2. Examples of common polymerization initiators include radical initiators such as organic peroxides and azo polymerization initiators.
[0089] Examples of the organic peroxide include peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxycarbonates, and peroxyesters.
[0090] Examples of the azo polymerization initiator include ADVN and AIBN. For example, 2,2-azobis(isobutyronitrile) (AIBN), 2,2-azobis(2-methylbutyronitrile) (AMBN), 2,2-azobis(2,4-dimethylvaleronitrile) (ADVN), 1,1-azobis(1-cyclohexanecarbonitrile) (ACHN), dimethyl-2,2-azobisisobutyrate (MAIB), 4,4-azobis(4-cyanovaleric acid) (ACVA), 1,1-azobis(1-acetoxy-1-phenylethane), 2,2-azobis(2-methylbutyramide), 2,2-azobis( 4-Methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2-methylamidinopropane) dihydrochloride, 2,2-azobis[2-(2-imidazolin-2-yl)propane], 2,2-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2-azobis(2,4,4-trimethylpentane), 2-cyano-2-propylazoformamide, 2,2-azobis(N-butyl-2-methylpropionamide), 2,2-azobis(N-cyclohexyl-2-methylpropionamide), etc.
[0091] If a polymerizable monomer that already contains a polymerization initiator is used in the second step, the polymerization initiator will be contained in the emulsion droplets when the O / W emulsion is formed, which makes it easier for the polymerization reaction to polymerize the monomer inside the emulsion droplets in the third step described below to proceed.
[0092] The weight ratio of the polymerizable monomer to the polymerization initiator in the second step is not particularly limited, but it is usually preferable that the polymerization initiator is 0.1 parts by mass or more per 100 parts by mass of the polymerizable monomer. If the polymerization initiator is less than 0.1 parts by mass, the polymerization reaction does not proceed sufficiently, and the yield of the composite particles 5 decreases, which is not preferable.
[0093] The polymerizable monomer may contain functional components other than the polymerization initiator in advance. Specific examples include magnetic materials, pharmaceuticals, agricultural chemicals, fragrances, adhesives, enzymes, pigments, dyes, deodorants, metals, metal oxides, inorganic oxides, etc. When the polymerizable monomer contains functional components other than the polymerization initiator in advance, the functional components can be contained inside the core particles of the manufactured composite particles 5, making it possible to express functions according to the application.
[0094] (Third step) The third step is a step of solidifying the droplets containing the core particle precursor 2 to obtain composite particles 5 in which the core particles 3 are covered with a microfibrillated cellulose layer 10 as shown in FIG.
[0095] The specific method for solidifying the droplets varies depending on the material of the droplets. When a polymerizable monomer is used, the polymerization method is not particularly limited and can be appropriately determined depending on the type of polymerizable monomer and the type of polymerization initiator used. One example of the polymerization method is suspension polymerization.
[0096] The specific suspension polymerization method is not particularly limited, and can be carried out using a known method. For example, the droplets can be solidified by heating the O / W emulsion obtained in the second step while stirring it. The stirring method is not particularly limited, and any known method can be used, specifically, a disperser or a stirrer can be used. In some cases, the mixture can be solidified by heat treatment alone without stirring. The temperature conditions during heating can be appropriately determined depending on the type of polymerizable monomer and the type of polymerization initiator, and may be, for example, 20° C. or higher and 150° C. or lower. If the temperature is lower than 20° C., the polymerization reaction rate may decrease, and if the temperature exceeds 150° C., the fine cellulose 1 may be denatured. The time for the polymerization reaction can be appropriately determined depending on the type of polymerizable monomer and the type of polymerization initiator, and may be, for example, about 1 hour to 24 hours. The polymerization reaction may be carried out by irradiation with ultraviolet light, which is a type of electromagnetic wave, or by irradiation with particle beams such as electron beams instead of electromagnetic waves.
[0097] When a thermoplastic polymer is used, the molten polymer is solidified by undergoing a phase transition. A typical method for the phase transition is cooling. In this case, the crystallinity of the thermoplastic polymer can be controlled by controlling the cooling rate. Specific examples of the cooling method include a method of diffusing the polymer in water or ice water, a method of contacting the polymer with a refrigerant such as liquid nitrogen, and a method of allowing the polymer to cool naturally.
[0098] When a non-curable polymer is used, it is solidified by removing the solvent. The method for removing the solvent is not particularly limited, and examples thereof include a heating method, a decompression method, an electromagnetic wave irradiation method, and a combination thereof.
[0099] When the third step is completed, a substantially spherical composite particle 5 is obtained in which a core particle 3 mainly composed of a polymer is covered with the micronized cellulose 1. In the composite particle 5 immediately after being obtained, the organic onium cation / ammonium ion 7a is bonded to at least a part of the micronized cellulose 1 present on the surface. The particle size of the composite particle 5 is relatively uniform, and the degree of uniformity is high.
[0100] The dispersion liquid immediately after the end of the third step is in a state in which composite particles 5, a large amount of water, and the finely divided cellulose 1 that is not integrated with the core particles 3 and is free are mixed together. Examples of recovery and purification methods for extracting only the composite particles 5 from this dispersion include washing by centrifugation and washing by filtration. A known method can be used for washing by centrifugation. For example, the composite particles 5 in the dispersion are precipitated by centrifugation, the supernatant is removed, and the composite particles 5 are redispersed in a water / methanol mixed solvent. Finally, the composite particles 5 can be recovered by removing the residual solvent from the precipitate obtained by centrifugation. A known method can also be used for filtration and washing. For example, the composite particles 5 can be recovered by repeatedly suction-filtering with water and methanol using a PTFE membrane filter with a pore size of 0.1 μm, and finally removing the residual solvent from the paste remaining on the membrane filter. In either case, the method for removing the residual solvent is not particularly limited, and the removal can be performed by air drying or heat drying in an oven. The dried solid material containing the composite particles 5 is obtained as a fine powder without being in the form of a film or aggregates.
[0101] (Fourth step) The fourth step is a step of removing the organic onium cation / ammonium ion 7a from the produced composite particle 5. The fourth step is carried out after the third step as necessary, and may be omitted if unnecessary in consideration of the use of the composite particle 5, etc.
[0102] As described above, in the composite particles 5 immediately after production, a part of the fine cellulose 1 has organic onium cations / ammonium ions 7a as counter ions. In cases where the presence of the organic onium cations / ammonium ions 7a is undesirable in relation to the use of the composite particles 5, or where it is desired to bond a cationic substance other than the organic onium cations / ammonium ions 7a to the fine cellulose 1 via an ionic bond, the organic onium cations / ammonium ions 7a may be removed by carrying out the fourth step.
[0103] An example of a method for removing the organic onium cation / ammonium ion 7a is ion exchange. The organic onium cation / ammonium ion 7a can be removed by dispersing the composite particles 5 having the organic onium cation / ammonium ion 7a in an aqueous solution containing an acidic compound, and then washing with pure water. After removing the organic onium cation / ammonium ion 7a, a desired cationic compound may be added, and a cationic substance different from the organic onium cation / ammonium ion 7a may be bound to the anionic functional group of the fine cellulose 1 by ionic bonding.
[0104] As described above, the composite particle 5 according to this embodiment has high bioaffinity and good dispersion stability derived from the fine cellulose 1 present on the surface as the fine cellulose layer 10.
[0105] In addition, since the core particles 3 are formed using finely divided cellulose 1 to which organic onium cations / ammonium ions 7a are bonded, a wide variety of resins can be used to form the core particles 3, resulting in composite particles that can be used for a wide variety of applications. For example, composite particles with thermoplasticity, which have been difficult to produce in the past, can now be easily produced.
[0106] Furthermore, the fine cellulose 1 acquires hydrophobicity due to the organic onium cation / ammonium ion 7a, and becomes amphiphilic. As a result, the yield of the composite particles 5 is significantly improved, and the particle size distribution is uniform, making it an excellent material.
[0107] The dry solid of the composite particle 5 exhibits the material properties of the fine cellulose 1, but is obtained as a fine powder, and since there is no aggregation between the particles, it can be easily dispersed again in a solvent. Since the fine cellulose 1 and the core particle 3 are inseparably bonded, the composite particle 5 shows a stable dispersion derived from the properties of the fine cellulose 1 even after redispersion.
[0108] The method for producing the composite particle 5 according to this embodiment allows for easy production of particles exhibiting the properties of the micronized cellulose 1 in a dry, tradeable state. Therefore, effects such as a low environmental impact, reduced transportation costs, reduced risk of spoilage, improved efficiency of addition as an additive, and improved efficiency of kneading with hydrophobic resins can be expected.
[0109] The present invention will be further described with reference to examples. The technical scope of the present invention is not limited to the specific contents of the examples. In the following description, "%" means "mass %" unless otherwise specified.
[0110] <Example 1> (First step: obtaining a fine cellulose dispersion) (TEMPO oxidation of wood cellulose) 70g of softwood kraft pulp was suspended in 3500g of distilled water, and a solution of 0.7g of TEMPO and 7g of sodium bromide dissolved in 350g of distilled water was added, and the mixture was cooled to 20℃. 450g of 2mol / L sodium hypochlorite aqueous solution with a density of 1.15g / mL was added dropwise to start the oxidation reaction. The temperature in the system was always kept at 20℃, and the pH was kept at 10 by adding 0.5N sodium hydroxide aqueous solution during the reaction. When the total amount of sodium hydroxide added relative to the weight of cellulose reached 3.50mmol / g, about 100mL of ethanol was added to stop the reaction. After that, filtration and washing with distilled water were repeated using a glass filter to obtain oxidized pulp. The obtained oxidized pulp was added to a hydrogen chloride aqueous solution adjusted to pH 2, dehydrated, and washed with water to perform the first acid treatment. Next, it was added to a hydrogen chloride aqueous solution adjusted to pH 3, dehydrated, washed with water, and performed the second acid treatment. After that, washing and dehydration were repeated to obtain a purified oxidized pulp.
[0111] (IR measurement of oxidized pulp) The oxidized pulp after the TEMPO oxidation reaction and washing with distilled water (before acid treatment), and the oxidized pulp after acid treatment with an aqueous hydrogen chloride solution and washing with water (after acid treatment) were sandwiched between slide glasses and dried at 70°C for 3 hours, and then FT-IR measurement was performed using the ATR method (JASCO Corporation, FT / IR-6300). The results are shown in Figure 4. After acid treatment, the oxidized pulp had a 1720cm -1 While the peak near the COO - 1600cm derived from -1 From the above, the peak near COO of oxidized pulp disappeared due to acid treatment. - It was confirmed that the Na group was completely replaced by the COOH group (H type).
[0112] (Measurement of carboxyl group content of oxidized pulp) After TEMPO oxidation, 0.1 g of the oxidized pulp was weighed out as solids and dispersed in water at a concentration of 1%, and hydrochloric acid was added to adjust the pH to 2.5. The amount of carboxyl groups (mmol / g) was then determined by conductometric titration using a 0.5 M aqueous solution of sodium hydroxide, which was 1.6 mmol / g.
[0113] (Introduction of organic onium cations by counterion substitution) Water was added to the oxidized pulp to prepare a suspension with a solids concentration of 5%, and 1.0 equivalent of tetrabutylammonium hydroxide (TBAH), an organic onium compound, was added as an alkaline species to the oxidized pulp carboxyl group. The mixture was stirred for 1 hour using a stirrer to obtain oxidized pulp with organic onium cations introduced by counterion substitution.
[0114] (Defibrillation treatment of counterion-substituted oxidized pulp) The counterion-substituted oxidized pulp obtained by the above method was dispersed in distilled water and refined for 30 minutes using a juicer mixer. If necessary, defoaming was performed using a centrifugal defoamer. This resulted in a dispersion of refined cellulose (TEMPO-oxidized CNF, CSNF) with a concentration of 1%. The resulting dispersion showed high transparency and thixotropy.
[0115] (Second step: Preparation of O / W type emulsion) As the core particle precursor, 10 g of the polymerizable monomer monofunctional acrylate, isobornyl acrylate (hereinafter also referred to as "IB-XA"), was used, and 1 g of the polymerization initiator, 2,2-azobis-2,4-dimethylvaleronitrile (hereinafter also referred to as "ADVN"), was dissolved in it. The entire amount of the IB-XA / ADVN mixed solution was added to 40 g of a 1% concentration fine cellulose dispersion. The IB-XA / ADVN mixed solution and the dispersion were separated into two phases, each with high transparency.
[0116] Next, the shaft of an ultrasonic homogenizer was inserted from the liquid surface of the upper phase of the mixture in a two-phase separation state, and ultrasonic homogenization was performed for 3 minutes under conditions of a frequency of 24 kHz and an output of 400 W. The mixture after ultrasonic homogenization became a cloudy emulsion. When a drop of the mixture was dropped onto a slide glass, sealed with a cover glass, and observed under an optical microscope, numerous emulsion droplets of IB-XA of about 1 to several μm were observed, and it was confirmed that the dispersion was stabilized as an O / W type emulsion.
[0117] (Third step: A step of obtaining composite particles coated with fine cellulose by solidifying the core particle precursor) The O / W emulsion dispersion was placed in a water bath at 70°C and stirred with a stirrer for 8 hours to carry out the polymerization reaction. After 8 hours of treatment, the dispersion was cooled to room temperature, the droplets were solidified, and composite particles were generated in the dispersion. There was no change in the appearance of the dispersion before and after the polymerization reaction. The resulting dispersion was centrifuged (75,000g, 5 minutes) to obtain a precipitate containing composite particles. The supernatant was removed by decantation to recover the precipitate, which was then washed repeatedly with pure water and methanol using a PTFE membrane filter with a pore size of 0.1 μm. The composite particles thus purified and recovered were redispersed in pure water at a concentration of 1%, and the particle size was measured using a particle size distribution analyzer (NANOTRAC UPA-EX150, manufactured by Nikkiso Co., Ltd.), revealing that the average particle size (median value) was 2.5 μm. The composite particles were air-dried and then vacuum-dried at room temperature of 25°C for 24 hours, resulting in a finely grained dry powder with no aggregation or film formation.
[0118] (Observation of the shape of composite particles using SEM) SEM images of the above-mentioned dry powder are shown in Figures 5 and 6. The magnification in Figure 5 is 100x, and the magnification in Figure 6 is 2000x in the upper left region and 50000x in the other regions. As can be seen from Figure 5, by carrying out the polymerization reaction using the O / W emulsion droplets as a template in the second and third steps, a large number of spherical composite particles 5 derived from the shape of the emulsion droplets were obtained, and the particles had a high degree of uniformity in diameter. It can be seen from Fig. 6 that the surface of the composite particle is evenly covered with fine cellulose 1 having a width of about several nm. Since Fig. 6 is an image after repeated filtration and washing, it was shown that in the composite particle 5 of the present invention, the core particle 3 and the fine cellulose 1 are bonded and inseparable. (Particle size distribution of composite particles) The particle size distribution of the above dry powder was measured using a particle size distribution analyzer LS-13320 manufactured by Beckman Coulter, Inc., and the results are shown in Figure 9. The particle size distribution was mostly within the range of 1 to 10 μm with a median value of 2.5 μm, and showed good agreement with the SEM image.
[0119] <Examples 2 to 4> Composite particles of Examples 2 to 4 were produced in the same manner as in Example 1, except that the following organic onium compounds were used instead of TBAH. Example 2 Tetramethylammonium hydroxide (TMAH) Example 3 Dimethylbenzylamine (DMBA) Example 4 Dimethylstearylamine (DMSA)
[0120] <Example 5> Composite particles of Example 5 were produced in the same manner as in Example 1, except that isobornyl methacrylate (IB-X), which is a monofunctional methacrylate, was used as the core particle precursor instead of IB-XA.
[0121] <Example 6> The composite particles of Example 6 were prepared in the same manner as in Example 1, except that p-methylstyrene (p-MeSt), which is a monofunctional vinyl monomer, was used as the core particle precursor instead of IB-XA.
[0122] <Example 7> The composite particles of Example 7 were produced under the same conditions as in Example 1, except that carboxymethylated CNF obtained by carrying out the carboxymethylation (hereinafter also referred to as "CM") treatment described in Patent Document 2 was used instead of TEMPO-oxidized CNF. CM-modified CNF exhibits high transparency.
[0123] <Example 8> Polycaprolactone (PCL, molecular weight 10,000) was used as the core particle precursor. In the second step, a 20% MEK solution of PCL was added to the fine cellulose dispersion. This dispersion was heated to 75°C and treated with an ultrasonic homogenizer to form an O / W emulsion, which was then cooled with ice water to solidify the droplets. The composite particles of Example 7 were produced under the same conditions as in Example 1 except for the above.
[0124] <Example 9> Composite particles of Example 9 were prepared in the same manner as in Example 8, except that DMBA was used instead of TBAH.
[0125] <Example 10> The composite particles of Example 10 were prepared in the same manner as in Example 1, except that the amount of TBAH added was 0.8 equivalents relative to the carboxyl groups of the oxidized pulp.
[0126] <Example 11> The composite particles of Example 11 were prepared in the same manner as in Example 1, except that the amount of TBAH added was 1.8 equivalents relative to the carboxyl groups of the oxidized pulp.
[0127] <Example 12> Composite particles of Example 12 were produced in the same manner as in Example 1, except that in the first step, the acid treatment was carried out only once. In Example 12, the substitution degree of the COOH group of the oxidized pulp determined by FT-IR measurement was 0.7. The substitution degree was determined by the 2870 cm -1 Based on the peak intensity at 1720cm -1 The peak intensity ratio (I1720 / I2870) is calculated and defined as the ratio when I1720 / I2870 in FIG.
[0128] <Examples 13 and 14> Composite particles of Examples 13 and 14 were prepared in the same manner as in Example 1, except that the following amines were used instead of the organic onium compound TBAH. Example 13 Stearylamine Example 14 Trihexylamine
[0129] <Comparative Example 1> Composite particles of Comparative Example 1 were produced in the same manner as in Example 1, except that untreated pulp that had not been subjected to the TEMPO oxidation treatment was used.
[0130] <Comparative Example 2> Composite particles of Comparative Example 2 were prepared in the same manner as in Example 1, except that sodium hydroxide, which is not an organic onium compound, was used instead of TBAH.
[0131] <Comparative Example 3> Composite particles of Comparative Example 3 were prepared in the same manner as in Example 5, except that sodium hydroxide, which is not an organic onium compound, was used instead of TBAH.
[0132] <Comparative Example 4> Composite particles of Comparative Example 4 were prepared in the same manner as in Example 6, except that sodium hydroxide, which is not an organic onium compound, was used instead of TBAH.
[0133] <Comparative Example 5> Composite particles of Comparative Example 5 were prepared in the same manner as in Example 7, except that sodium hydroxide, which is not an organic onium compound, was used instead of TBAH.
[0134] <Comparative Example 6> Composite particles of Comparative Example 6 were prepared in the same manner as in Example 8, except that sodium hydroxide, which is not an organic onium compound, was used instead of TBAH.
[0135] (Fourth step: Removing organic onium cations from composite particles 5) The dried powder of the composite particle 5 according to Example 1 was added to an aqueous hydrogen chloride solution of pH 2.5 so that the solid concentration was 1%, and the solution was treated with an ultrasonic cleaner for 5 minutes, and further stirred with a stirrer for 30 minutes. This resulted in a suspension with no visible aggregation. This suspension was concentrated by centrifugation (25000g, 10 minutes) and decantation, and then added to an aqueous hydrogen chloride solution of pH 4 and stirred with a stirrer for 5 minutes, and then further concentrated by centrifugation and decantation. Then, washing and concentration with pure water were repeated five times. The purified and collected composite particles were air-dried, and further vacuum dried at room temperature of 25 degrees for 24 hours to obtain a dried powder. When the obtained dried powder was analyzed by XPS, it was confirmed that the nitrogen source derived from TBAH was not detected, and the organic onium cation was removed. When the dried powder was added again to pure water and ultrasonicated, it showed good redispersion. The above treatment was carried out in all Examples, and removal of the organic onium cation and satisfactory redispersion were confirmed. In Comparative Examples, the fourth step was not carried out.
[0136] Table 1 shows a summary of the details of the examples and comparative examples.
[0137] [Table 1]
[0138] The evaluation results of the examples and comparative examples are shown in Table 2. The evaluation items and criteria are as follows. Composite particle yield (%) The weight was calculated as follows: weight (g) of the obtained composite particles / weight (g) of the resin of the core particle precursor used in the production×100. Average particle size (median value) of composite particles: Measured using a laser diffraction particle size distribution analyzer (Beckman Coulter, LS-13320). If any coarse resin lumps were present, they were removed before measurement. -Whether each process can be carried out (First step) ○ (Feasible): The transmittance of the dispersion liquid measured by a spectrophotometer (optical path length 1 cm, wavelength 600 nm) is 70% or more. × (Not practicable): The transmittance of the dispersion liquid measured by a spectrophotometer (optical path length 1 cm, wavelength 600 nm) is less than 70%. The low transmittance of the dispersion indicates that the cellulose is not finely divided. (Second process) ○ (Feasible): No change was observed in the total light transmittance of the O / W emulsion after being left to stand for 24 hours. × (Not feasible): The total light transmittance of the O / W emulsion changes significantly after standing for 24 hours, or separation is observed. Changes in the total light transmittance of an emulsion occur due to instability, such as separation or coalescence, of the emulsion. (Third step) ○(Feasible): A large number of spherical composite particles are obtained. × (Not feasible): Particles are not spherical or coarse aggregates of composite particles are observed. If the emulsion is highly stable, the emulsion droplets will maintain their shape after polymerization. On the other hand, if the emulsion becomes unstable before or during polymerization, it will separate or coalesce to produce irregularly shaped or coarse resin particles.
[0139] [Table 2]
[0140] As shown in Table 2, in each Example, the core particle precursor was stably formed into droplets in the micronized cellulose dispersion, and composite particles with small and uniform particle sizes were successfully formed in high yields. This is believed to be because a part of the hydrophilic CNF was hydrophobized by the organic onium cation derived from the organic onium compound, improving the adsorption force to the core particle precursor. In all of the comparative examples, it was not possible to perform all of the first to third steps satisfactorily, resulting in a low yield of composite particles and a low degree of uniformity of particle size.
[0141] 7 and 8 show SEM photographs of the dry powder of the composite particles according to Comparative Example 1. It can be seen from Fig. 7 that coarse composite particles were present in Comparative Example 1, and the particle size distribution was not uniform. In the coarse composite particles, most of the surface of the core particle was exposed, as shown in Fig. 8, and only a small amount of fine cellulose was bonded. [Industrial Applicability]
[0142] The composite particles according to the present invention have favorable effects from the viewpoint of industrial implementation, such as improved addition efficiency as an additive, improved kneading efficiency with resin, and contribution to cost reduction in terms of improved transport efficiency and prevention of spoilage. By utilizing the properties of the fine cellulose on the particle surface and the polymer constituting the core particle, the composite particles according to the present invention can be applied to coloring materials, adsorbents, cosmetic pigments, sustained-release materials, deodorants, antibacterial medical devices, antibacterial articles for personal care products, packaging materials, dye-sensitized solar cells, photoelectric conversion materials, photothermal conversion materials, heat shielding materials, optical filters, Raman enhancing elements, image display elements, magnetic powders, catalyst carriers, drug delivery systems, etc. [Explanation of symbols]
[0143] 1. Micronized cellulose 2. Core particle precursor (droplet) 3 Core particles 5 Composite particles 6. Cellulose raw materials 7. Organic Onium Compounds / Amines 7a Organic Onium Cations / Ammonium Ions 10 Micronized cellulose layer
Claims
1. a first step of defibrating an anionic cellulose raw material in a solvent containing an organic onium compound / amine to obtain a microfibrillated cellulose dispersion containing microfibrillated cellulose having an organic onium cation / ammonium ion bonded thereto and a number average minor axis diameter of 1 nm or more and 1000 nm or less; a second step of stabilizing the core particle precursor as an emulsion in an O / W emulsion in which the microfibrillated cellulose dispersion is made into a continuous layer and a core particle precursor containing a liquid polymerizable monomer and / or polymer is dispersed as oil droplets in the continuous layer; a third step of solidifying the core particle precursor to form a core particle, thereby obtaining a composite particle in which the core particle is covered with the finely divided cellulose inseparably bonded to the core particle; Equipped with the content of the anionic functional group in the fine cellulose having anionic properties is 0.1 mol or more and 5.0 mol or less per 1 g of cellulose, and the binding amount of the organic onium cation / ammonium ion is 0.8 equivalents or more and 2 equivalents or less relative to the anionic functional group; A method for producing composite particles.
2. The organic onium cation contains at least one atom selected from nitrogen, phosphorus, hydrogen, and sulfur. The method for producing the composite particle according to claim 1 .
3. the organic onium cation is a quaternary ammonium ion; The method for producing the composite particle according to claim 1 .
4. The method for producing composite particles according to claim 1 , wherein the amine is any one of a primary amine, a secondary amine, and a tertiary amine.
5. The core particle contains a polymer obtained by polymerizing at least one type of monomer having a polymerizable functional group. The method for producing the composite particle according to claim 1 .
6. The polymer contained in the core particle is a thermoplastic polymer. The method for producing the composite particle according to claim 1 .
7. The core particle contains a biodegradable material. The method for producing the composite particle according to claim 1 .
8. The method further comprises a fourth step of removing the organic onium cation / ammonium ion bound to the fine cellulose after the third step. The method for producing the composite particle according to claim 1 .
Citation Information
Patent Citations
Making of adhesive label
JP1984023370A
Formation of pattern
JP1984028339A
luminaire
JP1985020454A
Fine cellulose fiber
JP2008001728A
Method for producing cellulose nanofiber
JP2010216021A
